Remote reef cryptobenthic diversity: Integrating autonomous reef monitoring structures and in situ environmental parameters - Steyaert, Margaux; Lindhart, Mathilde; Khrizman, Alexandra; Dunbar, Robert B.; Bonsall, Michael B.; Mucciarone, David A.; Ransome, Emma; Santodomingo, Nadia; Winslade, Paige; Head, Catherine E. I. (Frontiers in Marine Science, 2022)
Coral reef sessile organisms inhabiting cryptic spaces and cavities of the reef matrix perform vital and varied functional roles but are often understudied in comparison to those on exposed surfaces. Here, we assess the composition of cryptobenthic taxa from three remote tropical reef sites (Central Indian Ocean) alongside a suite of in situ environmental parameters to determine if, or how, significant patterns of diversity are shaped by local abiotic factors. To achieve this, we carried out a point-count analysis of autonomous reef monitoring structure (ARMS) plate images and employed in situ instrumentation to recover long-term (12 months) profiles of flow velocity, wave heights, temperature, dissolved oxygen, and salinity, and short-term (3 weeks) profiles of light and pH. We recovered distinct environmental profiles between sampling sites and observed that ocean-facing reefs experienced frequent but short-lived cooling internal wave events and that these were key in shaping in situ temperature variability. By comparing temperature and wave height profiles recovered using in situ loggers with ex situ models, we discovered that global satellite products either failed to recover site-specific profiles or both over- and underestimated actual in situ conditions. We found that site choice and recruitment plate face (top or bottom) significantly impacted the percentage cover of bryozoans, gastropods, soft and calcified tube worms, as well as crustose coralline algae (CCA) and fleshy red, brown, and green encrusting macroalgae on ARMS. We observed significant correlations between the abundance of bryozoans, CCA, and colonial tunicates with lower mean temperature and higher mean dissolved oxygen profiles observed across sites. Red and brown encrusting macroalgae abundance correlated significantly with medium-to-high flow velocities and wave height profiles, as well as higher pH and dissolved oxygen. This study provides the first insight into cryptobenthic communities in the Chagos Archipelago marine-protected area and adds to our limited understanding of tropical reef sessile communities and their associations with environmental parameters in this region. With climate change accelerating the decline of reef ecosystems, integrating analyses of cryptobenthic organisms and in situ physicochemical factors are needed to understand how reef communities, if any, may withstand the impacts of climate change.